Fancy Nancy and the sensational babysitter - O'Connor, Jane.; Ivanov, A. (Aleksey); Ivanov, O. (Olga) (New York : HarperFestival, 2010)
Nancy is excited about her new babysitter coming over and has the whole evening planned out. But things don't turn out quite the way she expected. Her babysitter, Alex, is a teenager, but Alex is a boy, not a girl!
F
b
b